Xylitol promotes the antioxidant and biocontrol efficiency of the antagonistic yeast, Meyerozyma guilliermondii - Zhang, Weiwei; Zhuang, Shunyao; Gao, Jianshuang (Frontiers in Microbiology, 2025)
The biocontrol efficiency of the antagonist yeast Meyerozyma guilliermondii is significantly reduced under oxidative stress in adverse environments. However, effective strategies to improve M. guilliermondii under such abiotic stress remain limited. As an effective protectant of yeasts, xylitol has significant potential to improve the performance of M. guilliermondii under abiotic stress. We investigated xylitol’s effects on the viability and efficiency of M. guilliermondii under oxidative stress. The results showed that 0.5 M and 1 M xylitol significantly enhanced yeast survival, antioxidant gene expression, and enzyme activity, including thioredoxin reductase (TrxR) and peroxidase (POD), while reducing intracellular reactive oxygen species levels as well as damage to mitochondrial membranes, and preserving the ATP content. Notably, xylitol-treated (XT) yeast exhibited higher intracellular xylitol levels and improved resistance to oxidative stress compared with the non-xylitol-treated cells. Additionally, XT yeast showed a greater biocontrol efficacy and lower postharvest fungal infection rate by gray mold and blue mold in apples. These results demonstrated that xylitol effectively boosts the resilience and biocontrol efficiency of M. guilliermondii, making it a promising candidate to improve postharvest disease management.